PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP LOYALITAS KONSUMEN PADA RUMAH MAKAN ISTANA LELE DI KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Feriyanto, Yudi; Soeliha, Siti; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research purposed to determine the effect of service quality and location on consumer loyalty at Istana Lele restaurant in Banyuputih, Situbondo regency with consumer satisfaction as an intervening variable. The population was all visitors of Istana Lele restaurant. The sampling method used was simple random sampling by ignoring the population levels of this research. Data analysis and hypothesis testing in this research used Partial Least Squares -Structural Equation Modeling (PLS- SEM). The results of direct effect hypothesis test using smart PLS 3.0 application showed that service quality has a significant positive effect on consumer satisfaction. Location has a significant positive effect on consumer satisfaction. Service quality has a significant positive effect on consumer loyalty. Location has a positive but not significant effect on consumer loyalty. Consumer satisfaction has a significant positive effect on consumer loyalty. Service quality has a significant positive effect on consumer loyalty through consumer satisfaction. Location has a significant positive effect on consumer loyalty through consumer satisfaction.